PENERAPAN METODE PRAKTIKUM MATERI ASAM, BASA, DAN GARAM TERHADAP KETERAMPILAN PROSES SAINS SISWA SMP - Wildayati, Wildayati; Sartika, Rody Putra; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine differences in students 'science process skills before and after practicum methods are applied and to determine the magnitude of the improvement of practicum methods for students' science process skills in the material of Acid, Bases, and Salt Seventhegrade students’ of SMP Negeri 08 Pontianak. The form of research used was pre-experimental design with one-group pretest-posttest design research design. The sample selection technique is done by using purposive sampling technique. The data collection tools used were the initial Science Process Skills test instrument, the final Science Process Skills, and interview guidelines. The test questions are validated using the validity of the Gregory test. The test questions used in the form of essays with indicator indicators are observing, classifying and predicting and have a validity spread of 1 of the two validators with very high categories. Test questions are reliably using Cronbach alpha. The reliability result is 0.6 with a high category so that the test questions are feasible to use.There are differences in students' science process skills before and after practicum methods applied in Acid, Basa, and Salt material for Seventhegrade students’ of SMP Negeri 08 Pontianak. From the N-Gain calculation results obtained by 0.4 with the medium category, this shows that learning with practicum methods has an enhancement on the science process skills in acid, basic, and salt Seventhegrade students’ of SMP Negeri 08 Pontianak.Keywords: Practical Method, Science, Acid, Base, Salt Process Skills